Iron and Calcium Biomineralizations in the Pampean Coastal Plains, Argentina: Their Role in the Environmental Reconstruction of the Holocene - Osterrieth, Margarita Luisa (2018)
Biomineralizations are biogenic composites, crystalline or amorphous,produced by the metabolic activity of organisms distributed all over the world. Theaim of this work was to evaluate the presence of iron and calcium biomineralizationsand their influence in the physicochemical and mineralochemical variations inpaleo and actual pedosedimentary sequences of the coastal plains in Mar Chiquita.The complex interaction of calcium with iron biomineralizations, as framboidal andpoliframboidal pyrites associated with gypsum, barite, calcite, halite, and iron oxyhydroxides,have demonstrated the active and complex biogeochemistry that occursin the temperate?wet paleoesturaries and estuaries of the coastal Pampean Plains.Particularly the consequences that different human activities could have.